(untitled) (Jurnal kesehatan komunitas (Journal of community health), 2021)
Background: DHF is the most serious vector-borne disease in Bandar Lampung. Dengue virus and its vector Aedes aegypti are sensitive to weather changes, especially rainfall, temperature, and humidity. Objective: This study aims to determine the relationship between weather factors and dengue cases using 2009-2018. Methods: The data were obtained from reports on the number of monthly cases of the Bandar Lampung City Health Office and daily climate reports from the Meteorology, Climatology, and Geophysics Agency, converted into monthly averages. The SPSS 24.0 was used at all levels of analysis (CL = 95%), including Pearson Correlation, Spearman rank Correlation, and Multiple Linear Regression. Results: We found the highest cases of DHF are in January, February, and March. Rainfall has a positive correlation with the number of dengue cases in 2011 (p-value = 0.012) and 2015 (p-value = 0.020). Each year, the rainy period precedes the start of the increase in dengue cases. Temperature has a negative correlation in 2014 (p-value = 0.036). Humidity has a positive correlation in 2014 (p-value = 0.024), and 2015 (p-value = 0.018). Rainfall has the greatest influence on DHF cases in Bandar Lampung City (36.9%). Conclusion: These findings provide empirical evidence regarding the relationship between weather factors and DHF transmission and are expected to provide a scientific basis for the prevention and control of DHF.